Back-to-front: improved tactile discrimination performance in the space you cannot see. - Kóbor, I; Füredi, L; Kovács, G; Spence, C; Vidnyánszky, Z (2006)
We investigated any differences in people's ability to reconstruct the appropriate spatiotemporal ordering of multiple tactile stimuli, when presented in frontal space (a region where visual inputs tend to dominate) versus in the space behind the back (a region of space that we rarely see) in professional piano players and in non-musicians. Even though tactile temporal order judgments were much better in the musicians overall, both groups showed a much reduced crossed-hands deficit when their hands were crossed behind their backs rather than at the front. These results suggest that because of differences in the availability of visual input, the spatiotemporal representation of non-visual stimuli in front versus rear space is different.